How Large Is the Risk of Stagflation in the Eurozone? - Markus Demary; Michael Hüther (Intereconomics)
Abstract The rapid recovery of demand combined with supply constraints has led to rising prices during the past months. This is evident in oil and gas markets, but also in international trade, which has been thrown out of step by bottlenecks at Asian ports. This situation creates a trade-off for the European Central Bank, because a more expansionary monetary policy cannot mitigate the supply bottlenecks and supply-side restrictions, while a more restrictive monetary policy would slow down the economic recovery. For this reason, key interest rate hikes in the eurozone are not to be expected for 2022. If the supply-side factors become persistent and wage policy tries to pass the price effects on, monetary policy will be forced to become restrictive.